Enhancing Student Motivation in Arabic Language Learning through the Cooperative Integrated Reading and Composition (CIRC) Model: A Case Study in Islamic Schools of Banten - Nur Afif (AL-ISHLAH: Jurnal Pendidikan, 2024)
Arabic language proficiency is vital in Islamic education to understand religious texts and strengthen connections to Islamic heritage. Despite its importance, motivation in learning Arabic often remains low among students. This study aims to evaluate the Cooperative Integrated Reading and Composition (CIRC) model’s effectiveness in enhancing student motivation in Arabic language learning. A quasi-experimental design with a pretest-posttest control group was employed, involving 60 students from Islamic schools in Banten. Participants were divided equally into an experimental group, taught using the CIRC model, and a control group, which followed conventional methods. Data were collected through validated motivation scales, classroom observations, and interviews. The experimental group demonstrated a significant increase in motivation scores, from an average of 62.5 to 80.3, compared to a smaller improvement in the control group (61.7 to 65.4). Observational data revealed greater student engagement, active participation, and collaborative efforts in the CIRC group. Interviews confirmed that the collaborative elements of the CIRC model fostered enthusiasm, peer interaction, and confidence among students. The findings underscore the CIRC model’s potential to create an engaging and interactive learning environment, enhancing student motivation in Arabic language classes. The collaborative framework of CIRC appears to address diverse student needs effectively. Implementing the CIRC model in Islamic schools could significantly improve Arabic language learning outcomes. Future studies should explore its long-term impact on language proficiency and application across various subjects and educational contexts.